A comparative study of technical aspects of resistance spot brazed and resistance spot welded joints. (3rd April 2022) - Jafari Vardanjani, Mehdi
Abstract: Different joining methods are always chosen based on their features and capabilities for desired performance. Welding and brazing are among the frequent processes from which resistance spot welding (RSW) and resistance spot brazing (RSB) are chosen for many purposes. Although these methods have been in use for years in usual applications, making the best choice among them might require compromises and considerations. In this study, RSW and RSB methods are investigated and compared in terms of features, parameters, equipment, and capabilities. Two case studies have also been briefly reviewed to analyze different aspects of the methods. As results indicate, it has been inferred that RSW has been mostly functional for larger assemblies, with shorter process times, higher automatability, and longer dynamic stability, while RSB has been more logical for dissimilar sheet material joining, with lower processing temperatures, more stability for static loads, and more portability. In terms of defects, RSW joints have been more prone to expulsion, corrosion on grain boundaries, and solidification cracks, while RSB joints have been affected particularly by brittle cracks, and trapped gas voids in brazed metal.